OPTIMALISASI KOMODITAS LOKAL PISANG RAJA BULU UNTUK MEWUJUDKAN DESA WIRAUSAHA BERKELANJUTAN DI DESA JEPANG PAKIS MELALUI PPK ORMAWA - Mardhiyah Utami; Siti Afrikhatul Muna; Rifa Fajriah Marta Praja; Dwi Naddine Indrawati; Naili Sarifatul Izah; Sarah Nabela; Malichatuz Zahro Assaidah; Savitri Wanabuliandari (Jurnal Hilirisasi IPTEKS, 2025)
Villages are one of the important pillars of national economic development, so that increasing local potential and empowering communities are key to village independence. The village of Jepang Pakis, Jati District, Kudus Regency, has a superior potential in the form of raja bulu bananas with a harvest of ±16,000 kg per year. However, its utilization is still limited to selling raw products at low prices, so it does not provide significant added value to the community. This condition is caused by a lack of innovation in processed products, weak business management, and limited marketing strategies. To overcome these problems, the Student Organization Capacity Building Program (PPK Ormawa) of UKM BISMA, Muria Kudus University, implemented community empowerment through the concept of the Raja Bulu Banana Entrepreneurial Village (Dewi Prabu) based on sustainability. The method used is Participatory Action Research (PAR) by involving the Women Farmers Group (KWT) and PKK mothers as active partners in the process of identifying potential, group discussions, product diversification training, business management assistance, digital marketing, and participatory evaluation. The initiative resulted in seven innovative banana-based products that are environmentally friendly and support the zero-waste concept: Sendookies, Golden Bana, Greenana Flour, EcoNana, Sunbana Leaf, Banaleaf Craft, and Bananique.This program has successfully improved entrepreneurial skills, fostered new business groups, expanded marketing, and strengthened the branding of entrepreneurial villages. Thus, the optimization of pisang raja bulu through product innovation has proven to increase economic added value, promote a green economy, and create sustainable entrepreneurial villages based on local potential.